NEEDS ANALYSIS ON DEVELOPING A SYLLABUS OF ENGLISH FOR THE STUDY PROGRAM OF DEVELOPMENT ECONOMICS UNIVERSITAS BRAWIJAYA - Agus Gozali (Fakultas Ilmu Budaya, Universitas Brawijaya, 2018)
Abstract: Needs analysis plays an important role in developing curriculum of English for Specific Purposes (ESP). This study investigated the needs and views of Study Program of Development Economics (SPDE) students of ESP courses. There were three types of instruments used, a set of questionnaire for the students of SPDE, interview checklists for the English lecturer and the head of study program, and documents. The result of the study showed that the syllabus should facilitate the ability to communicate in English on academic, general, and vocational situation in the economics field. The English course should also focus the students on reading skill.